Effect of bisphenol A toxicity on growth performance, biochemical variables, and oxidative stress biomarkers of Nile tilapia, Oreochromis niloticus (L.) - Abdel‐Tawwab, Mohsen; Hamed, Heba S. (Journal of applied ichthyology, 2018)
Bisphenol A (BPA) is one of the industrial chemical compound which is used in the production of polycarbonate plastics and epoxy resins. BPA is used throughout the world and it could enter the aquatic ecosystems causing serious problems. To evaluate the potential effects of BPA toxicity on Nile tilapia, Oreochromis niloticus (L.) performance, its lethal concentration (LC50) was determined and it was 13.13 µg/L. After that, fish (33.9 ± 0.55 g/fish) were exposed to 0.0, 1.64, or 3.28 µg/L of BPA for 6 weeks after which growth performance, biochemical variables, and oxidative defense system were assessed. The results showed that fish growth and feed intake were significantly reduced as BPA levels increased with no significant difference in fish survival. Total protein, albumin, globulin, and acetylcholine esterase decreased significantly; meanwhile, aspartate transferase, alanine transferase, alkaline phosphatase, uric acid, and creatinine increased significantly with exposure to BPA in a dose dependent manner. Furthermore, malondialdehyde value and the activities of superoxide dismutase and catalase increased significantly; while glutathione peroxidase and glutathione S‐transferase decreased significantly as BPA levels increased. In conclusion, BPA exposure in aquatic environment deteriorated fish performance and health causing liver and kidney dysfunction. Thus, fish exerted oxidative defense enzymes as a protection tool against BPA toxicity.